Aanalisis Dominasi Pengaruh On Tthe Job Training Terhadap Peningkatan Kualitas Kinerja - Dewi, Santi Riana (Jurnal Manajemen, 2018)
In order to support the realisation of Making Indonesia 4.0 through the increasing of the quality of human resources, it has been done the dominant analysis of the influence of the on the job training to the improvement of the employee performance in a company. While the result obtained are expected to have an impact to the management policy and decision making which is related to the effort to increase the employee performance quality. And at the end, the employee deliver the best performance and the best quality product to meet the consumer expectation. The research used descriptive and correlative design, with test of validity, normality, reliability, variance homogenity, independency test and t test to validate the hypothesis. The research conclude that the frequency of the on the job training should be increased to meet the superior employee performance quality in line with company profitability concern in the future.Keywords: on the job training, performance, influence, dominant, and improvement.